Peran Kompetensi Manajerial Kepala Madrasah dalam Meningkatkan Kualitas Pendidikan - Kalrina, Ririn; Astuti, Mardiah; Hidayat; Atika, Nyimas (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2024)
This study aims to analyze the managerial competencies of the head of the madrasah at MTs N 1 Prabumulih. Through a qualitative approach with descriptive methods, data were collected from interviews, observations, and documentation. Key informants included the head of the madrasah, the student affairs vice principal, the curriculum vice principal, and teachers. The results show that the head of the madrasah possesses managerial competencies that include human resource management, strategic planning, and program development to enhance the performance of teachers and students. Additionally, the head of the madrasah is also capable of communicating effectively with various stakeholders and facing challenges in madrasah management. These findings highlight the importance of systematic planning and collaboration between the head of the madrasah and their team in achieving quality educational goals.